أهم القطاعات الطحلبية القاعية السائدة في عدة مناطق من الشاطئ السوري (شمال مدينة اللاذقية) - اسماعيل مهيب (Latakia University Journal -Biological Sciences Series, 2019)
تتأثر حياة وتوزع الطحالب القاعية السائدة في المنطقة الشاطئية الوسطى ( منطقة المد والجزر) بمجموعة من العوامل البيئية على الشاطئ الممتد شمال مدينة اللاذقية مسافة 7 كم بدءاً من حوض مسبح أفاميا حتى شاطئ رأس ابن هاني شمالاً , والتي تم فيها تحديد أربع محطات دراسية لأخذ العينات بشكل دوري ومنتظم (مرتين في الشهر) على العمق 0,5 - 1 م بمعدل عشر عينات كمية من كل محطة ليبلغ المجموع 80 عينة على مدى عامين ( 2008-2009 ) وعدة عينات كيفية (نوعية) . تميزت المنطقة الشاطئية المدروسة بوجود قطاعين طحلبيين أساسيين هما القطاع الأول الشمالي يضم 46نوعاً طحلبياً , تغطيته 50- 57 % من سطح القاع, والقطاع الثاني الجنوبي( شمال مدينة اللاذقية مباشرة) يضم61 نوعاً طحلبياً, تغطيته 45% من سطح القاع , كلا القطاعين يميزان المياه الملوثة بالنفايات المنزلية والمخلفات النفطية لكنهما مختلفان بالتركيز. The life and distribution of benthic algae dominant in middle coastal area (midlittoral zone) is affected by a group of ecological factors on the Syrian coast located 7 Km north of Lattakia city; from Aphamia summing boll until Ras Ibn Hanee shore in the North, where four study stations have been determined for quantitative samples (Twice a month), from 0.50 - 1 M deeps, in average 10 quantitative samples were collected from each station (in total 80 samples during 2008-2009, plus several qualitative samples) The studied coastal areas have been distinguished by the existence of two essentials algae sectors: first Northern algae sector: Crystoseiretum- Sargasossum consist of 46 algae species covered by 50-57% benthic surface, the second Southern algae sector (in the North Lattakia city directly) Enteromorphetum – Ulvosum consist of 61 algae species, covered by 45% benthic surface. The two studied sectors are distinguished by home waste water, and oil waste in deferent concentrations.